The dynamics of multidimensional educational poverty - Azaz Ali Ather Bukhari; Hooi Hooi Lean; Waqar Ali Ather Bukhari; Saqlain Raza; Amber Pervaiz (Data Science and Management)
Education is a cornerstone in promoting the overall welfare of individuals and plays a pivotal role in shaping their lives. As the developing world grapples with the multifaceted challenges of poverty, there is a growing emphasis on evaluating poverty from a multidimensional perspective. Therefore, this study estimates the educational poverty index (EPI). To construct the EPI, Alkire and Foster’s methodology was used with data from the Pakistan Panel Household Survey. We also estimated the dynamics of educational poverty using logistic regression. The results show that the EPI declined from 0.24 in 2001 to 0.21 in 2010. Similarly, the intensity decreased from 0.42 to 0.30. However, the incidence of educational poverty increased from 0.58 to 0.69. At the provincial level, there was a reduction in educational poverty and intensity across all provinces. However, the rate of decline in the EPI and intensity was comparatively higher in Baluchistan than in other provinces. Most of the population belonged to the transitory poor category (0.47). Other dynamic factors such as the household head’s age, education, family size, disability, and land acres also play vital roles in moving into or out of poverty. Our study reveals numerous dimensions that can increase household educational poverty. The government should be vigilant while preparing the policy and must consider the multiple dimensions of a household to eradicate educational poverty.